Leptin Restores Endothelial Function via Endothelial PPARγ-Nox1–Mediated Mechanisms in a Mouse Model of Congenital Generalized Lipodystrophy. Issue 6 (December 2019) - Bruder-Nascimento, Thiago; Faulkner, Jessica L.; Haigh, Stephen; Kennard, Simone; Antonova, Galina; Patel, Vijay S.; Fulton, David J.R.; Chen, Weiqin; Belin de Chantemèle, Eric J.
Abstract : Leptin is the current treatment for metabolic disorders associated with acquired and congenital generalized lipodystrophy (CGL). Although excess leptin levels have been associated with vascular inflammation and cardiovascular disease in the context of obesity, the effects of chronic leptin treatment on vascular function remain unknown in CGL. Here, we hypothesized that leptin treatment will improve endothelial function via direct vascular mechanisms. We investigated the cardiovascular consequences of leptin deficiency and supplementation in male gBscl2 −/− ( Berardinelli-Seip 2 gene–deficient) mice—a mouse model of CGL. CGL mice exhibited reduced adipose mass and leptin levels, as well as impaired endothelium-dependent relaxation. Blood vessels from CGL mice had increased NADPH Oxidase 1 (Nox1) expression and reactive oxygen species production, and selective Nox1 inhibition restored endothelial function. Remarkably, chronic and acute leptin supplementation restored endothelial function via a PPARγ-dependent mechanism that decreased Nox1 expression and reactive oxygen species production. Selective ablation of leptin receptors in endothelial cells promoted endothelial dysfunction, which was restored by Nox1 inhibition. Lastly, we confirmed in aortic tissue from older patients undergoing cardiac bypass surgery that acute leptin can promote signaling in human blood vessels. In conclusion, in gBscl2 −/− mice, leptin restores endothelial function via peroxisome proliferator activated receptor gamma-dependent decreases in Nox1. Furthermore, we provide the first evidence that vessels from aged patients remain leptin sensitive. These data reveal a new direct role of leptin receptors in the control of vascular homeostasis and present leptin as a potential therapy for the treatment of vascular disease associated with low leptin levels. Abstract : Supplemental Digital Content is available in the text.